1992
DOI: 10.1128/jvi.66.8.4966-4971.1992
|View full text |Cite
|
Sign up to set email alerts
|

The matrix protein of human immunodeficiency virus type 1 is required for incorporation of viral envelope protein into mature virions

Abstract: Accumulating evidence suggests that the matrix (MA) protein of retroviruses plays a key role in virus assembly by directing the intracellular transport and membrane association of the Gag polyprotein. In this report, we show that the MA protein of human immunodeficiency virus type 1 is also critical for the incorporation of viral Env proteins into mature virions. Several deletions introduced in the MA domain (p17) of human immunodeficiency virus type 1 Gag polyprotein did not greatly affect the synthesis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(194 citation statements)
references
References 39 publications
12
179
1
Order By: Relevance
“…In particular, phosphorylation of MA on a C-terminal tyrosine has been shown to be crucial for the nuclear import of the viral preintegration complex and for virus replication in MDM (Gallay et al, 1995a,b). However, others have reported conflicting results that indicate that neither the N-proximal basic cluster nor the C-terminal tyrosine of MA contribute selectively to HIV-1 replication in MDM (Freed et al, , 1997Fouchier et al, 1997) MA is essential for the incorporation of HIV-1 Env protein spikes into nascent viral particles (Yu et al, 1992b;Dorfman et al, 1994). Small alterations throughout the globular core of HIV-1 MA blocked the incorporation of autologous Env protein, but not that of amphotropic murine leukemia virus (A-MLV), a widely divergent oncoretrovirus Mammano et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phosphorylation of MA on a C-terminal tyrosine has been shown to be crucial for the nuclear import of the viral preintegration complex and for virus replication in MDM (Gallay et al, 1995a,b). However, others have reported conflicting results that indicate that neither the N-proximal basic cluster nor the C-terminal tyrosine of MA contribute selectively to HIV-1 replication in MDM (Freed et al, , 1997Fouchier et al, 1997) MA is essential for the incorporation of HIV-1 Env protein spikes into nascent viral particles (Yu et al, 1992b;Dorfman et al, 1994). Small alterations throughout the globular core of HIV-1 MA blocked the incorporation of autologous Env protein, but not that of amphotropic murine leukemia virus (A-MLV), a widely divergent oncoretrovirus Mammano et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…arrangement, termed maturation, wherein the CA molecules condense to form the conical core particle that encapsidates the RNA-NC ribonucleoprotein complex, and the matrix proteins form a shell that remains associated with the inner face of the viral membrane (Gelderblom, 1991;Hoglund et al, 1992;Marx et al, 1988). Genetic analyses indicate that the matrix shell helps to anchor the transmembrane envelope protein (TM, gp41) on the surface of the virion, because mutations in both MA (Dorfman et al, 1994;Freed & Martin, 1996;Yu et al, 1992) and the intraviral domain of TM , 1996Mammano et al, 1995; can produce envelope-deficient virions.…”
mentioning
confidence: 99%
“…Previous reports have shown that the interaction between the matrix protein and the cytoplasmic domain of envelope proteins was required for the incorporation of the envelope proteins into mature viral particles [33,34,47]. Indeed, we saw a lower infection efficiency with the NDV-pseudotyped HIV-Luc virus compared to the VSV-G pseudotyped HIV-Luc virus ( Figure 2C), which we associated with a less-optimal interaction between the HIV-1 matrix and the cytoplasmic domain of NDV envelope proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NDV-pseudotyped HIV-Luc viral particle was successfully produced, the infection efficiency was found to be over 34-fold lower than with the VSV-G-pseudotyped HIV-Luc virus (P,0.01) ( Figure 2C). We hypothesized that this may be due to the impact of the cytoplasmic domain of the envelope proteins [33,34]. To address this, four plasmids containing mutant HN or F were constructed ( Figure 1A (Figure 3).…”
Section: Factors Affecting the Infection Efficiency Of Ndv-pseudotypementioning
confidence: 99%